Efeitos sistêmicos e na superfície ocular de cães submetidos à instilação de cetorolaco de trometamol por 30 dias - Sônego, Dábila Araújo (2023)
This study aimed to evaluate whether the instillation of a non-steroidal antiinflammatory ophthalmic solution based on trometamol ketorolac for 30 consecutive days may change the blood count, the serum biochemistry profile, and the urinalysis of healthy dogs. Eleven small breed dogs (2.9-10 kg), with ages ranging from 2 to 10 years were enrolled in the study. Dogs received 40 μL of 0.4% trometamol ketorolac eye drops, every each 12 h in both eyes for 30 consecutive days. Blood and urinary samples were collected at baseline, and following 15 and 30 days of the beginning of the treatment. Creatinine levels increased significantly at day 15 (1.21 ± 0.1 mg/dL) and 30 (1.22 ± 0.1 mg/dL) when compared with baseline (0.94 ± 0.1mg/dL) (p < 0.01). Significantly increased values of serum potassium were observed only at day 30 (4.66 ± 0.15 mEq/L), when compared with day 15 (4.32 ± 0.12 mEq/L) and baseline (4.36 ± 0.15 mEq/L) (p < 0.05). The other hematological and biochemical parameters did not change significantly during the study (p > 0.05). Despite significance, both creatinine and potassium remained within the reference range for the species. The other hematological, biochemical and urinary parameters did not change significantly during the study (p > 0.05), concluding that the instillation of trometamol ketorolac for 30 days did not cause relevant changes in these parameters in healthy dogs.